Fenologia e qualidade de carthamus tinctorius l. em diferentes populações e épocas de cultivo - Rocha, Edileusa Kersting da (2005)
This work had as objectives to test different populations of the culture of cartamo, regarding the behavior of the fenology, the characteristics of the stem, the cycle and the behavior of the border plants at two cultivation periods: fall/winter and spring/summer. The populations used in the two periods were 48, 64, 80, 96, 112 and 128 pl/m2. The fall/winter cultivation corresponded to the period from 04/04/2003 to 23/08/2003 and the spring/summer cultivation corresponded to the period from 03/10/2003 to 23/12/2003. The cycle, of the emergency to the end of harvesting, lasted 142 days for the first period and 74 days for the second cultivation period. Flowering lasted langer for the fall/winter and was very short for the spring/summer cultivation. The total and partial plant height did not differ among populations in the fall/winter cultivation. However, in the spring/summer the total height presented a quadratic behavior with the increase in population and the partial height did not vary. In the fall/winter cultivation the plants presented larger values of stem diameter, branches diameter, length of branches and total number of nodes. The stem diameter, branches diameter, number and length of branches, fresh and dry matter mass decreased with the increase in population at the two cultivation times. The capitulus diameter decreased with the increase in population at the fall/winter, but at the spring/summer it decreased in the populations of 48 to 96 pl/m2 and increased in the populations of 112 to 128 pl/m2. The border plants in the fall/winter cultivation presented values of fresh matter, total and partial height, stem diameter and of branches, capitulus diameter and length of branches, higher than the observed for the plants of the interior of the flower bed.